Absolute measurement of radiative and Auger rates of K-shell-vacancy states in highly charged Fe ions - Steinbrügge, René; Bernitt, Sven; Epp, S. W.; Rudolph, Jan K.; Beilmann, Christian; Bekker, Hendrik; Eberle, Sebastian; Müller, A.; Versolato, O.; Wille, H.-C.; Yavaş, H.; Ullrich, Joachim; et al. (Physical review. A, Atomic, molecular, and optical physics, 2015)
We present absolute measurements of radiative and Auger decay rates of K−shell vacancies in highly charged iron ions. The ions were resonantly excited with monochromatic x rays from the PETRA III synchrotron source. By measuring x-ray fluorescence and Auger decay simultaneously, absolute transition rates could be determined independently of most experimental parameters. The results confirm theoretical calculations, which are essential to model the photoexcited plasmas in x-ray binary stars and active galactic nuclei.
Gesehen am 22.06.2020